Highly Enantioselective Synthesis of N‐Unprotected Unnatural α‐Amino Acid Derivatives by Ruthenium‐Catalyzed Direct Asymmetric Reductive Amination - Hu, Le'an; Wang, Yuan‐Zheng; Xu, Lei; Yin, Qin; Zhang, Xumu (Angewandte Chemie International Edition, 2022)
An unprecedented highly enantioselective Ru‐catalyzed direct asymmetric reductive amination of α‐keto amides with ammonium salts has been disclosed, efficiently offering valuable enantioenriched N‐unprotected unnatural α‐amino acid derivatives bearing a broad range of aryl or alkyl α‐substituents. This protocol features easily accessible substrates, good functional‐group tolerance and excellent enantiocontrol, making it a good complementary approach to the known methods. Moreover, this method is also applicable to the preparation of N‐unprotected unnatural α‐amino acid derivatives containing an additional stereogenic center at the β‐position through a dynamic kinetic resolution (DKR) process. Convenient transformations of the obtained products into chiral N‐unprotected unnatural α‐amino acids, drug intermediates, peptides, and organocatalysts/ligands further showcase the utility of this method. An unprecedented Ru‐catalyzed direct asymmetric reductive amination of α‐keto amides with ammonium salts has been achieved. This protocol provides an efficient and practical way for the synthesis of diverse enantioenriched α‐aryl‐ or alkyl‐substituted N‐unprotected unnatural α‐amino acids and N‐unprotected β‐branched α‐amino acids. Further follow‐up transformations enable access to drug intermediates, peptides, and organocatalysts/ligands.